2008
DOI: 10.1167/iovs.07-0879
|View full text |Cite
|
Sign up to set email alerts
|

Early Activation of Inflammation- and Immune Response-Related Genes after Experimental Detachment of the Porcine Retina

Abstract: Differentially expressed genes in the retina early after experimental detachment are mainly related to inflammation and immune responses, intracellular proteolysis, and protection against oxidative stress. A local immune and inflammatory response may represent a major causative factor for reactive changes in the retina after detachment. The inflammatory response is not restricted to the detached retina but is also observed in the nondetached retina; this response may underlie functional changes in these region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
45
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 42 publications
2
45
0
2
Order By: Relevance
“…Interestingly, HMGB1 appeared to be robustly upregulated in both the photoreceptors and the other retinal cells at day 3 after RD inductions, and DAPI staining was inversely downregulated at the same time ( Figure 2b, e and h). As previous reports demonstrated that dramatic alterations of retinal gene expression occurred after RD, 31 this high level of HMGB1 expression might be related to the active gene transcription. HMGB1 in the nucleus might be stress responsive and necessary for proper transcription after RD tissue damage.…”
Section: Hmgb1 Is Present In Cultured Retinal Cell and Released Extramentioning
confidence: 68%
“…Interestingly, HMGB1 appeared to be robustly upregulated in both the photoreceptors and the other retinal cells at day 3 after RD inductions, and DAPI staining was inversely downregulated at the same time ( Figure 2b, e and h). As previous reports demonstrated that dramatic alterations of retinal gene expression occurred after RD, 31 this high level of HMGB1 expression might be related to the active gene transcription. HMGB1 in the nucleus might be stress responsive and necessary for proper transcription after RD tissue damage.…”
Section: Hmgb1 Is Present In Cultured Retinal Cell and Released Extramentioning
confidence: 68%
“…48 In addition, NFB induces the expression of genes involved in chronic and acute inflammatory responses, 49 which concurred with the association of both HtrA1 and VEGF with inflammation. 38,50 Further studies should be conducted to validate this hypothesis. Unlike the previous studies, 16,17 we found no association between vitreous HtrA1 levels and rs11200638 genotypes (Table 4).…”
Section: Discussionmentioning
confidence: 95%
“…2) might be related to inflammatory and stress responses. [37][38][39] HtrA1 is associated with geographic atrophy 29 and drusen, 30,31 and is upregulated in response to estrogeninduced oxidative stress. 40 We also found that human fetal RPE cells responded to chemical-induced stress by simultaneous upregulations of HTRA1 and VEGFA after treatments with tunicamycin and DTT (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…After retinal injury, such as retinal detachment, Müller cells upregulate inflammatory factors, including monocyte chemoattractant protein-1, which recruit phagocytotic monocytes/macrophages and microglial cells to the injured area [40,41]. Invading macrophages and neutrophils release oxygen free radicals and cytotoxic cytokines, which play critical roles in photoreceptor apoptosis after retinal detachment [42] and in neuronal degeneration after ischemia-reperfusion [43].…”
Section: Müller Cell Gliosismentioning
confidence: 99%
“…Likewise, argon laser photocoagulation slows photoreceptor degeneration by induction of bFGF in Müller cells [52]. Other neuroprotective effects of gliosis include the production and release of antioxidants, such as glutathione (see below), pyruvate, α-ketoglutarate, metallothionein, lysozyme, ceruloplasmin, heme oxygenase and reduced ascorbate [41,53,54,55,56,57,58]. Müller cells phagocytize cellular debris [59] and blood-derived proteins (fig.…”
Section: Müller Cell Gliosismentioning
confidence: 99%